A Study on Material of Manikin Skin for Measuring Clothing Evaporative Resistance (Journal of Fiber Bioengineering and Informatics, 2015)
Evaporative resistance is an important parameter of clothing in its thermal comfort. The sweating\rthermal manikin developed for evaporative resistance test needs a textile skin covering its surface to\rsimulate sweating. To investigate the effect of skin material on the measurement, three knitted fabrics\r(cotton, blend of cotton and polyester, polyester) were made into skins for the sweating thermal manikin\rNewton. The evaporative resistances of boundary air layer and four clothing ensembles were measured\runder an isothermal condition. It was found that the evaporative resistances measured with cotton skin\rwere smaller than those measured with the other two skins. The large evaporative area and strong water\rabsorbing ability of thick, dense and hydrophilic cotton skin result in more evaporative heat loss and\rconsequently lower evaporative resistance values.